Desenvolvimento de um dispositivo para acionamento de joystick de cadeira de rodas motorizada - Paiva, Thiago Sá de (2020)
According to the World Health Organization (WHO), about 15% of the world's population (above one billion people) live with some form of disability, and 2-4% live with extreme difficulty. The National Health Survey (from the portuguese acronym PNS) estimates that in Brazil 1.3% of country's population live with physical disability, and about half of them with severe limitation. Tetraplegia is a highly incapacitating condition, defined as partial or total paralysis of all limbs and torso. It has multiple origins, and the most common is spinal cord injury. Regarding the Brazilian population, its incidence rate was estimated as being 71 new cases per million inhabitants in a recent study, finding itself above the world average. Taking all of the above into account, it is noticeable a great need for assistive technology both in Brazil and worldwide. Unfortunately, as pointed out by WHO only one in every ten people have access to these technologies. Actions were taken in the last few years seeking to boost assistive technology development, both nationally and internationally, where we can highlight national research programs like PGPTA (from the portuguese Programa de Apoio à Pós-Graduação e à Pesquisa Científica e Tecnológica em Tecnologia Assistiva no Brasil) and global initiatives like WHO's GATE (Global Cooperation on Assistive Technology). Additionally, Universal Design performs an important role on product development in general, not only on assistive technologies and products, through its principles that aim to include all potential users on technology and product conception, resulting in better solutions. The purpose of this work is to provide an equipment capable of adapting a conventional EPW (Electrically Powered Wheelchair) to alternative commands without interfering with EPW’s original design, emulating through alternative inputs what would be performed by user’s upper limbs, making it usable for tetraplegic users and broadening the public that utilizes a conventional EPW. The proposal consists of a hardware and software solution to adapt a conventional EPW joystick to alternative inputs. From the use of a Personal Computer (PC) mouse cursor, making use of X and Y movement coupled with click function, the user selects through buttons on an interface which joystick function he/she wants, like the press of a button or movement of the handle in the direction of interest for driving. A functionality test was executed using a free, open source, webcam based mouse emulator program, and it was possible to verify that the solution was capable of executing all tasks. Considerations regarding execution time were made, highlighting some concern with activating time. In the end, future work suggestions were presented.